How to Deal with Clinical Teaching in Times of a Covid-19 Pandemic? [Como Lidar Com O Ensino Clínico No Tempo de Uma Pandêmica Covid-19?] [¿Cómo Enfrentar la Enseñanza Clínica en Tiempos de Pandemia por Covid-19?] - Monje-Aguero, E; Nunez-Carrasco, E; Baeza-Contreras, M (Universidad de Concepcion, 2020)
[No abstract available]